UV-vis spectroscopic and dielectric properties of bismuth borosilicate glasses doped with potassium chromate - Jirapan Dutchaneephet (2018)
© 2017, Chiang Mai University. All rights reserved. Bismuth borosilicate glasses doped with various amounts of potassium chromate (Cr doping) were prepared by a normal melt quenching technique. The glass texture was clear and bubble free and the glass colors changed from light green to opaque green with increased Cr doping. The glass density was found to vary with Cr doping, and the maximum density of about 3.34 g/cm 3 was obtained in the specimen doped with 0.5 mass% Cr. The UV-Vis spectra of Cr doped glass showed a strong UV absorption with a sharp increase of transmission spectra beyond the so-called cutoff wavelength, and it was found to shift to a longer wavelength from about 397 nm to 506 nm as the Cr doping content increased from 0.02 to 3%. Thecutoff wavelengths of Cr doped glasses and the Cr doping content were found to reflect a logarithmic relationship. Furthermore, the increase of Cr doping was found to affect not only the opacity of the glass but also the shift of the characteristic wavelengths from about 537 nm to 576 nm. Results from dielectric measurement showed that both dielectric constant and loss tangent were rather low, with the values deviating in the range of about 12-23 and 0.1-0.5 at 1 kHz respectively.